Quality of Life in Patients With Untreated and Symptomatic Hallux Valgus. (November 2016) - Yamamoto, Yohei; Yamaguchi, Satoshi; Muramatsu, Yuta; Terakado, Atsushi; Sasho, Takahisa; Akagi, Ryuichiro; Endo, Jun; Sato, Yasunori; Takahashi, Kazuhisa
Background: The purposes of this study were to compare the quality of life (QOL) of subjects who had untreated symptomatic hallux valgus with the QOL of the general population and to investigate factors associated with the QOL of the subjects. Methods: One hundred sixteen subjects with previously untreated and symptomatic hallux valgus were surveyed. QOL was assessed using the 36-item Short Form Health Survey (SF-36). Additionally, clinical evaluations (the visual analog scale for pain, Japanese Society for Surgery of the Foot Scale, lesser toe pain, and pain in other parts of the body) and radiographic evaluations (hallux valgus angle, intermetatarsal angle between the first and second metatarsals, and dislocation of the second metatarsophalangeal joint) were performed. Differences in the SF-36 between the subjects and the general population were tested using independent t tests. Correlations between the QOL measurements, clinical evaluations, and radiographic evaluations were assessed using Spearman rank correlation coefficient. Results: All SF-36 subscales and physical component summary scores for the subjects were significantly lower than those of the general population. Notably, the standardized physical function subscale (38.2 ± 15.8, P < .001) and physical component summary scores (38.9 ± 14.5, P < .001) were more than 10 points lower than those of the general population. Most QOL and clinical evaluation parameters were not correlated or were negligibly correlated with radiographic evaluations. Similarly, lesser toe pain or pain in other parts of the body was not correlated with QOL or clinical evaluations. Conclusion: The QOL of untreated and symptomatic hallux valgus subjects was lower than that of the general population. All QOL and clinical evaluation parameters were not significantly or negligibly correlated with the severity of toe deformities. Surgical decision making should not be based on the severity of the deformity alone, but rather patient QOL should also be carefully assessed. Level of Evidence: Level III, comparative series.